2016
DOI: 10.4081/hpr.2016.5453
|View full text |Cite
|
Sign up to set email alerts
|

Mood changes after indoor tanning among college women: associations with psychiatric/addictive symptoms

Abstract: Indoor tanning (IT) has been linked with psychiatric and addictive symptoms, and frequent tanning may indicate tanning dependence (addiction). The current study evaluated the effects of an IT episode on mood states and the association of these effects with psychiatric and addictive symptoms among young adult female indoor tanners. One-hundred thirty-nine female university students aged 18-25 years who had indoor tanned completed an online survey including the Positive and Negative Affects Scales and a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The strength of association was greater than studies reporting comorbidities associated with non-dependent tanning behavior and comparable to those reported for indoor tanning dependence (18, 20, 54). This evidence, in conjunction with research indicating indoor tanning can produce mood-enhancing effects (11, 14, 15), suggests a potential mechanism whereby young women experiencing depressed mood or other psychological distress may indoor tan because it alleviates such symptoms. However, there remains a need for research to understand how psychiatric comorbidity, affect-oriented motives, and indoor tanning dependence unfold over time.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The strength of association was greater than studies reporting comorbidities associated with non-dependent tanning behavior and comparable to those reported for indoor tanning dependence (18, 20, 54). This evidence, in conjunction with research indicating indoor tanning can produce mood-enhancing effects (11, 14, 15), suggests a potential mechanism whereby young women experiencing depressed mood or other psychological distress may indoor tan because it alleviates such symptoms. However, there remains a need for research to understand how psychiatric comorbidity, affect-oriented motives, and indoor tanning dependence unfold over time.…”
Section: Discussionmentioning
confidence: 72%
“…Exposure to UV light among frequent tanners has been shown to activate reward-based brain regions (13) and to produce increased dopamine response (11) similar to other forms of addiction. Frequent indoor tanners have also been observed to endorse responses characteristic of drug exposure after tanning, such as improved mood and euphoria (14, 15). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interventions were delivered to male and female adult beachgoers given their likely engagement in intentional UVR exposure at the beach (Mahler, Kulik, Gibbons, Gerrard, & Harrell, 2003; Mahler, Kulik, Gerrard, & Gibbons, 2006; Pagoto, McChargue, & Fuqua, 2003; Pagoto, Schneider, Oleski, & Bodenlos, 2010). Heckman and colleagues’ (2016) web-based intervention targeted young adults between 18 and 25 years old (66% women) who were at elevated risk for skin cancer (e.g., light hair or eye color, sun sensitivity, sunburn history) based on a brief screening assessment. Although excessive tanners would be eligible for these studies, most participants reported infrequent tanning at baseline.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Tanners receive positive comments on their appearance from peers and family members and believe that tanning leads to greater social acceptance and is positively valued among peers (Banerjee, Campo, & Greene, 2008; Noar et al, 2014). Some tanners also find the experience of tanning to be relaxing and report mood-enhancing properties of UVR exposure (Heckman, Darlow, Cohen-Filipic, & Kloss, 2016; Noar et al, 2014). The reinforcing effects of tanning may explain why some individuals tan far more frequently than required to acquire and maintain a cosmetic effect.…”
mentioning
confidence: 99%